2013
DOI: 10.1242/jeb.091009
|View full text |Cite
|
Sign up to set email alerts
|

Complex vibratory patterns in an elephant larynx

Abstract: SUMMARYElephants' low-frequency vocalizations are produced by flow-induced self-sustaining oscillations of laryngeal tissue. To date, little is known in detail about the vibratory phenomena in the elephant larynx. Here, we provide a first descriptive report of the complex oscillatory features found in the excised larynx of a 25year old female African elephant (Loxodonta africana), the largest animal sound generator ever studied experimentally. Sound production was documented with high-speed video, acoustic me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
23
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 54 publications
(60 reference statements)
4
23
0
Order By: Relevance
“…Focusing on species that vocalize at these two extremes of the frequency range relevant in the animal realm, researchers found evidence that the production of infrasonic and ultrasonic vocalizations could be explained by the same mechanisms as those used in the human voice. For instance, Herbst and colleagues showed that infrasonic elephant rumbles result from MEAD-generated vocal fold oscillation, and that the infrasonic character of these oscillations is causally linked to the size and three-dimensional movements of these vocal folds (Herbst et al, 2012(Herbst et al, , 2013b. A similar conclusion was drawn regarding the production of ultrasonic vocalizations in rats by using ELE (Johnson et al, 2010) and intratracheal pressure and airflow measurements in anesthetized animals (Riede, 2011).…”
Section: Progressive Use Of Excised Larynx Experimentation In a Paralmentioning
confidence: 81%
See 1 more Smart Citation
“…Focusing on species that vocalize at these two extremes of the frequency range relevant in the animal realm, researchers found evidence that the production of infrasonic and ultrasonic vocalizations could be explained by the same mechanisms as those used in the human voice. For instance, Herbst and colleagues showed that infrasonic elephant rumbles result from MEAD-generated vocal fold oscillation, and that the infrasonic character of these oscillations is causally linked to the size and three-dimensional movements of these vocal folds (Herbst et al, 2012(Herbst et al, , 2013b. A similar conclusion was drawn regarding the production of ultrasonic vocalizations in rats by using ELE (Johnson et al, 2010) and intratracheal pressure and airflow measurements in anesthetized animals (Riede, 2011).…”
Section: Progressive Use Of Excised Larynx Experimentation In a Paralmentioning
confidence: 81%
“…To investigate such cases through ELE, special attention should be paid to avoid removing inner laryngeal tissue, in order to identify potential vibrating sources (e.g. Herbst et al (2013b) identified a 1:1 phase-locked vibration of vocal folds and ventricular folds in a elephant larynx). Another study using ELE on two red deer larynges documented increased glottal efficiency for non-regular vocal fold vibration regimes at high subglottal pressures, hypothetically suggesting an energetic advantage in animal vocal communication when converting metabolic to acoustic energy in this species (Herbst, 2014).…”
Section: Progressive Use Of Excised Larynx Experimentation In a Paralmentioning
confidence: 99%
“…Experimental data testing these hypotheses directly on real air sacs are currently lacking. One possible area of research, which is likely to prove fruitful, is ex-vivo investigation of the effects of air sacs on call acoustics in excised larynx experiments (see Titze et al, 2010;Klemuk et al, 2011;Herbst et al, 2012Herbst et al, , 2013Bowling et al, 2017;Garcia et al, 2017). Another exciting area, which would provide data on vocal-fold vibration during natural vocalizations (thus accounting for the 'source' of the sound, and allowing for the 'filter' to be analysed -Fant, 1960;Chiba and Kajiyama, 1941), is invivo electroglottography (Brown and Cannito, 1995;Herbst and Dunn, 2018).…”
Section: The Function Of Air Sacs In Primate Vocal Communicationmentioning
confidence: 99%
“…Such relationships between structure and behavior can be analyzed with the phase diagram (also called phase plot, phase space, or structure-behavior diagram) (Sterman, 2000). A phase diagram plots two variables on a two-dimensional graph (Herbst et al, 2013) with independent and dependent variables plotted on the X and Y axes, respectively. Since understanding structurebehavior associations is an important prerequisite for designing policies (Davidsen, 1992), the dynamic relationships were explored between key variables in the model and their policy implications were analyzed.…”
Section: Structure-behavior Analysismentioning
confidence: 99%